Using media to enhance Arabic speaking skills among Malay learners - Che Haron, Sueraya; Sheikh Ahmad, Ismail; Mamat, Arifin; Ahmed Mohamed, Ismaiel Hassanein (International Institute for Science, Technology & Education (IISTE), 2012)
This paper describes a study to investigate strategies to enhance Arabic speaking skills using media conducted on good and poor Malay speakers of Arabic. It highlights the similarities and the differences in terms of the types of media used by both groups of speakers, the activities commonly performed while using the media and the frequency of using the media. Finally the paper suggests some strategies for teachers, schools and universities to use media as a means to develop Arabic speaking skills.